2015
DOI: 10.1186/s10194-015-0507-7
|View full text |Cite
|
Sign up to set email alerts
|

Linear interictal pain in Epicrania Fugax

Abstract: Epicrania Fugax is a paroxysmal, short-lasting, head pain moving across one hemicranium, describing a linear or zag trajectory, starting and ending in territories of different nerves. Between attacks, patients are usually free of symptoms. We describe an Epicrania Fugax patient complaining of interictal pain. The interictal pain was line-shaped and extended across the usual starting and ending points of the typical Epicrania Fugax paroxysms. Although rarely encountered, persistent linear pain may be a feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
(4 reference statements)
1
8
0
1
Order By: Relevance
“…On the other hand, LH may be associated with EF. Pareja and Bandrés recently reported a patient with long-lasting linear interictal pain between the attacks of EF, and this interictal pain is similar to the LH pain (Pareja and Bandres, 2015 ). Wang et al have proposed that this linear interictal pain may be LH triggered by EF (Wang et al 2015 ), as EF can trigger the attacks of migraine and cluster headache (Jin and Wang, 2013 ), and LH has many clinical features similar to that of migraine (Wang et al 2014b ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, LH may be associated with EF. Pareja and Bandrés recently reported a patient with long-lasting linear interictal pain between the attacks of EF, and this interictal pain is similar to the LH pain (Pareja and Bandres, 2015 ). Wang et al have proposed that this linear interictal pain may be LH triggered by EF (Wang et al 2015 ), as EF can trigger the attacks of migraine and cluster headache (Jin and Wang, 2013 ), and LH has many clinical features similar to that of migraine (Wang et al 2014b ).…”
Section: Discussionmentioning
confidence: 87%
“…Table 2 summarizes the main clinical features of the twenty LH cases that have been described so far: twelve cases in the original description by Wang et al ( 2014b ) and eight new cases in the present communication. Pareja et al reported another possible one but the clinical description is not full (Pareja and Bandres 2015 ). Up to now, there has been a female predominance (1.5:1), and the age at onset has ranged from 20 to 73 years old (mean 41.8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical pain trajectory of EF is different from that of the currently reported coronal line-shaped head pain, whereas, recent reports have shown that the pain trajectory of EF may distribute in different area (de la Cruz et al 2015 ), even in multiple directions (Cuadrado et al 2015 ). Furthermore, Pareja and Bandres reported an interictal persistent line-shaped head pain in EF (Pareja and Bandres 2015 ). Thus, apparently, it should be considered that the current coronal line-shaped head pain may essentially be the interictal pain of EF.…”
Section: Discussion and Evaluationmentioning
confidence: 99%
“…Recientemente Wang et al (2014) han propuesto también la posibilidad de que un dolor similar en cuanto a su topografía, pero estático y sin componente dinámico (llamado por los autores cefalea lineal) pueda ser considerado una variante de una EF. Pareja et al (2015), en una carta al director, expone su opinión al respecto (que el autor de esta tesis comparte). Así, en la fase de consolidación del síndrome EF no parece adecuado renunciar al componente dinámico que se antoja como lo más característico de este síndrome.…”
Section: Criterios Diagnósticos Del Apéndice De La Cic-3unclassified